Angela N. H. Creager and Jean-Paul Gaudillière: Risk on the table: food production, health, and the environment - Francois, Jean R. (My University, 2024)
Food safety is an age-old but quotidian societal issue that has remained a concern throughout human history. The matter is gaining more significance in today’s globalized era, where minor food issues can now have extensive repercussions, impacting lives and economies worldwide in a very short time. In Risk on the Table: Food Production, Health, and the Environment, Angela Creager, Professor in History of Science at Princeton University, and Jean- Paul Gaudillière, Historian at Cermes3 and Professor at École des Hautes Études en Sciences Sociales, Paris, have assembled a compelling anthology that explores how scientific developments, industrial practices, and regulatory frameworks have shaped and responded to the risks associated with food production and consumption in modern society.